Reintegrasi dan Kontekstualisasi Kearifan Lokal Sintuwu Maroso: Upaya Menjawab Tantangan Pendidikan di Era Revolusi Industri 4.0 Menuju Society 5.0 - Adrisal Kaliongga; Ade Iriani; Mawardi Mawardi (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
All facets of life and life levels have been significantly impacted by the effects of the Industrial Revolution 4.0 and the Society 5.0. The two states also apply to the academic institutions. The efforts to address the concerns and obstacles in education and learning in this research attempt to define the technique of integrating and contextualizing the indigenous local knowledge of Sintuwu Maroso. Therefore, the realist ethnographic research had been used. To comprehend the cultural events, social facts must be studied in schools within their natural environments, with the assistance of research tools in the form of instructions for conducting interviews, observations, and documentaries. The Spradley ethnographic research model was employed for the data analysis. According to the findings, incorporating and contextualizing the values of Sintuwu Maroso local knowledge would assist forming the students' personalities so they can think critically, creatively, ingeniously, and integrative about current concerns in the society that arise in the digital age. To perform an inclusive education in the digital age, the school staff members should reflect on the values in the Sintuwu Maroso local wisdom.